2019
DOI: 10.1167/iovs.19-27378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retinal Pigment Epithelium Layer Change in Vogt-Koyanagi-Harada Disease With Multicontrast Optical Coherence Tomography

Abstract: PURPOSE. Clinical evaluation of retinal pigment epithelium (RPE) change is important for the therapeutic management of chronic Vogt-Koyanagi-Harada (VKH) disease. We evaluated longterm change in the RPE layer in VKH disease, using near-infrared (NIR; 817 nm) images and autofluorescence images at 488 nm (short-wavelength [SW]-AF) and 785 nm (NIR-AF), and compared those images with images from multicontrast optical coherence tomography (MC-OCT). MC-OCT is capable of simultaneous measurement of OCT angiography, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
(63 reference statements)
1
7
0
1
Order By: Relevance
“…From the MC-OCT dataset, we derived RPE-melanin-specific contrast OCT (RPE-melanin OCT) images, which we used to evaluate RPE changes 26 . In our previous studies of patients with AMD 26 and patients with Vogt-Koyanagi-Harada disease 25 , we confirmed similarities between NIR-AF images and RPE-melanin OCT projection images. Thus, the combination of RPE-melanin OCT and AF imaging might be useful for evaluation of RPE changes in PED.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…From the MC-OCT dataset, we derived RPE-melanin-specific contrast OCT (RPE-melanin OCT) images, which we used to evaluate RPE changes 26 . In our previous studies of patients with AMD 26 and patients with Vogt-Koyanagi-Harada disease 25 , we confirmed similarities between NIR-AF images and RPE-melanin OCT projection images. Thus, the combination of RPE-melanin OCT and AF imaging might be useful for evaluation of RPE changes in PED.…”
supporting
confidence: 84%
“…Therefore, RPE-melanin thickness maps do not represent the actual thickness of RPE-melanin, although they are proportional to the thickness of the RPE-melanin. Seventh, a threshold of F RPE (≥ 0.15) in MC-OCT imaging was used to calculate the area of RPE melanin defects, in accordance with the method used in our previous studies 9,25,26 . With this threshold, the RPE-melanin line at the normal RPE band occasionally became unclear (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we speculated that a few changes might be occurring at the level of the retinal pigment epithelium (RPE) that is causing these changes. While few imaging studies have analyzed RPE, both following the resolution of the disease and in the chronic phase, describing features such as focal areas of reversible RPE thickening and RPE atrophy, there is a lacuna in the literature regarding RPE imaging characteristics during the acute phase and immediately following resolution of the disease [ 8 , 9 , 10 ]. Thus, in the current study, we aimed to assess the morphological features of the more easily scanned RPE during the acute phase of the disease and following resolution and its probable role as a biomarker for the diagnosis and assessing the severity of VKH.…”
Section: Introductionmentioning
confidence: 99%
“…Ebenso können sich granuläre Läsionen mit erhöhter NIA-Intensität zeigen, die sich im weiteren Verlauf abschwächen. Diese Läsionen sind mit der FAF nicht eindeutig darstellbar [26].…”
Section: Entzündlich Und Autoimmun Bedingte Chorioretinopathienunclassified